O Treino de Força no Futsal: Uma Nova Abordagem Metodológica - Marques, Diogo Luís Sequeira Torgal (2019)
Made available in DSpace on 2019-01-04T17:08:22Z (GMT). No. of bitstreams: 1 5562_11324.pdf: 950593 bytes, checksum: 1a7a698a21afa323f2057668c3a69b1e (MD5) Previous issue date: 2017-07-14